2008
DOI: 10.1111/j.1439-037x.2008.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cold and Heat Tolerance of Winter‐grown Canola (Brassica napus L.) Cultivars by Pollen‐based Parameters

Abstract: Winter‐grown canola (Brassica napus L.) production is limited mostly by frost and winter kill in the southern canola‐growing regions of the United States. Tolerance to cold and heat were assessed by studying percentage of pollen viability (PV), in vitro pollen germination (PG) and pollen tube length (PTL) for 12 field‐grown cultivars. Freshly collected pollen from all cultivars were incubated on artificial solid growth media at a constant temperature ranging from 10 to 35 °C at 5 °C interval for 30 h to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 56 publications
(131 reference statements)
4
49
0
2
Order By: Relevance
“…The severity or extent of such effects depended on the degree of cold tolerance of the cultivars. In vitro pollen growth assays have been considered as a possible screen to identify germplasm, with the potential for improved reproductive stress tolerance (Kakani et al, 2002(Kakani et al, , 2005Salem et al, 2007;Singh et al, 2008). It was concluded that in susceptible types, low temperatures reduced the number of pollen mother cells and their ability to produce pollen, and that difference in tolerance between genotypes suggested that the character was polygenic (Gonalez et al, 1986).…”
Section: Effect Of Midseason Cold Stress On Pollen Production and Viamentioning
confidence: 99%
“…The severity or extent of such effects depended on the degree of cold tolerance of the cultivars. In vitro pollen growth assays have been considered as a possible screen to identify germplasm, with the potential for improved reproductive stress tolerance (Kakani et al, 2002(Kakani et al, , 2005Salem et al, 2007;Singh et al, 2008). It was concluded that in susceptible types, low temperatures reduced the number of pollen mother cells and their ability to produce pollen, and that difference in tolerance between genotypes suggested that the character was polygenic (Gonalez et al, 1986).…”
Section: Effect Of Midseason Cold Stress On Pollen Production and Viamentioning
confidence: 99%
“…The growth and development processes, such as stem elongation, leaf initiation and expansion, leaf area development, photosynthesis, flowering and fruiting of many crops including maize, are highly dependent on growth temperature (Tollenaar 1989a, b;Kim et al 2007, Singh et al 2008a, Li et al 2010. Yield and seed quality of many crops including maize are sensitive to frequently observed temperature extremes, and both to ambient and elevated UV-B radiation levels (Teramura et al 1990, Kim et al 2007, Ballare et al 2011, Yin and Wang 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, with 64-72% of genes in vegetative tissues of Tradescantia and maize also being expressed in pollen (reviewed by Hamilton and Mascarenhas, 1997), in vitro pollen germination has been investigated as a rapid screening criterion for tolerance to a variety of agronomically-important characteristics including soil acidity and salinity, metal and herbicide toxicity, as well as for heat tolerance (Sari-Gorla and Frova, 1997). Exposure to high temperatures reduces in vitro pollen germination percentage and pollen-tube length in many crops including canola (Singh et al 2008;Morrison et al 2016), cotton (Kakani et al 2005Song et al 2015), and sorghum (Nguyen et al 2013;Djanaguiraman et al 2014;Singh et al 2015Singh et al , 2016, as well as legumes like chickpea (Cicer arietinum; Devasirvatham et al 2012), field pea (Pisum sativum; Petkova et al 2009;Lahlali et al 2014;Jiang et al 2015), groundnut (Arachis hypogaea; Kakani et al 2002), and soybean (Glycine max; Koti et al 2005;Salem et al 2007). In sorghum, seed-set percentage (the number of seeds filled at physiological maturity divided by the total number of florets) was strongly and positively associated with in vitro pollen germination across genotypes and temperature regimes (Nguyen et al 2013;Singh et al 2015Singh et al , 2016.…”
Section: Introductionmentioning
confidence: 99%